A Promising Flight-Navigation Complex with an Intelligent Component - Selezneva, M.S.; Babichenko, A.V.; Neusypin, K.A.; Proletarsky, A.V.; Muratov, I. V. (2019 26th Saint Petersburg International Conference on Integrated Navigation Systems (ICINS), 2019)
The structure of the aircraft flight-navigation complex, capable of changing its architecture depending on the interference level and flight conditions, is developed. The algorithmic support of the complex additionally includes an intelligent component, consisting of self-organization algorithm, a dynamic database and a criterion for comparing the forecast and the current state of the complex. A integration algorithm is developed. The integration algorithm includes the original criterion for the degree of observability of state variables, which allows forming the optimal complex structure.